The indigenous polychromatic painting in the codices: Borgia and Nuttall - Rangel Díaz, Gabriela (2019)
Received: 31-08-2019Approved: 09-16-2019 The present work explores the relationship between the aesthetic and historical composition of the Borgia and Nutall codices, both forged within the Mixtec culture, whose conceptions are deeply ritual, linked to the mythological, religious, augustic and heroic, among others. The Borgia codex is located in the Vatican Apostolic Library and the Nutall in the British Museum both documents are highly prized for their stylistic, artistic, technical and polychromatic compositions that reflected more than the culture of the time, a way of seeing and interpreting the world through myth, form and color.